Canal reconstruction and mastoid obliteration using floating cartilages and musculoperiosteal flaps. (7th September 2016) - Lee, Ho Jun; Chao, Janet Ren; Yeon, Yeung Kyu; Kumar, Vijay; Park, Chan Hum; Kim, Hyung‐Jong; Lee, Jun Ho
Abstract : Objectives: To reduce the mastoid cavity‐associated problems secondary to canal wall down mastoidectomy, we designed a new surgical procedure that includes canal wall reconstruction using free‐floating cartilages and double musculoperiosteal flaps. Study Design: Retrospective study. Materials and methods: Thirty‐three patients were enrolled in this study. Preoperative and postoperative pure tone audiometry/speech discrimination score and postoperative status (complications and EAC status) were analyzed. Results: Air conduction thresholds were statistically improved ( P = 0.008). The air–bone gap was significantly reduced following surgery ( P = 0.001). There were no other major complications in any of the patients. Long‐term follow‐up demonstrated gradual widening of the neo‐EAC in 18 patients (54.5%) but normal contour of the neo‐EAC in the other 13 patients (39.4%). In just one case did the neo‐EAC become extremely widened. Conclusion: Mastoid obliteration and canal wall reconstruction using free‐floating cartilages and double musculoperiosteal flaps is very useful to achieve optimal surgical view, eliminate the middle ear pathology, and prevent recurrence of cholesteatoma and cavity problem. Level of Evidence: 4. Laryngoscope, 127:1153–1160, 2017